The use of serious games in engaging stakeholders for disaster risk reduction, management and climate change adaption information elicitation. (October 2020) - Fleming, K.; Abad, J.; Booth, L.; Schueller, L.; Baills, A.; Scolobig, A.; Petrovic, B.; Zuccaro, G.; Leone, M.F.
Abstract: Disaster Risk Reduction (DRR), Disaster Risk Management (DRM), and Climate Change Adaptation (CCA) involve a variety of stakeholders with different backgrounds, organizational frameworks, divergent concerns, and sometimes competing agendas. This requires forums where such groups can meet in order to enhance understanding, reconcile different views, and potentially assist each other in meeting their respective goals. One means of establishing such an exchange involves serious games . During the ESPREssO (Enhancing Synergies for disaster Prevention in the European Union) project, three such games, referred to as RAMSETE (Risk Assessment Model Simulation for Emergency Training Exercise), were developed. They were based on table-top, role-playing, scenario-based exercises, and their purpose was for stakeholder information elicitation about policy issues related to DRR, DRM, and CCA. Participants in the exercises were assigned roles where they interacted and negotiated in order to deal with the presented scenarios. The scenarios were primarily concerned with selecting an optimal set of policies to deal best with the issue in question. The games, while sometimes including an operational element, were meant to examine the motivations behind the decisions made, rather than to test or to train in response protocols. The participants in general found the games to be useful for framing discussions about complex issues, while their problem-solving character was appreciated and enjoyed. Such games allow stakeholders to openly discuss and challenge ideas, policies, and processes in a manner they would not normally do in their daily activities, with other professionals who they would not necessarily be in frequent contact with.